MELAMPAUI JAM KANTOR: MENYINGKAP LANSKAP KESEJAHTERAAN KARYAWAN GENERASI Z DAN MILENIAL DI INDUSTRI PERBANKAN - Ni Komang Ayu Cipta Dewi; I Putu Dharmawan Pradhana (CV. Lafadz Jaya, 2026)
The changing dynamics of work in the digital era have blurred the boundaries between working time and personal time, particularly in the banking industry, which is characterized by high job demands and working hours that frequently exceed formal regulations. This study aims to explore the perceptions and experiences of Generation Z and Millennials regarding their professional and personal well-being within the context of intensive and often demanding work environments. Using a qualitative approach through in-depth interviews with young employees from several banking institutions, this study identified various factors influencing their well-being, including workload, organizational culture, organizational support, and expectations for flexibility and meaningful work. The findings indicate that the majority of respondents experience difficulties in maintaining work-life balance due to excessive workloads and the absence of clear boundaries between working and personal time. Although most respondents appreciate the career stability and financial benefits offered by the banking industry, they also emphasize the importance of mental health, adequate rest, and recognition of personal needs as integral components of overall well-being. Therefore, this study recommends that banking institutions develop more adaptive human resource management strategies that align with the values and needs of younger generations, including flexible work arrangements, mental health support, and a more humane organizational culture. This study is expected to contribute to a better understanding of the well-being landscape of younger generations in the financial sector while serving as a reference for formulating policies that promote workforce sustainability.